Identidad social del grupo de jóvenes bailarines de la danza “electro” en el Distrito de San Juan De Lurigancho - Ortiz Jimenez, Juan Alexander Hector (2022)
This research describes the characteristics of social identity such as sense of belonging, positive or negative appreciation and affection that young people feel when they are part of the group (endogroup), in addition to the meaning given by others groups of dance styles, external to the main group (exogroup). With a qualitative methodology and phenomenological approach, twelve semi structured interviews were conducted with young people between 18 and 25 years of age who practice an urban dance style called Electro Dance, belonging to different districts of Metropolitan Lima of San Juan de Lurigancho to dance. Among the results, the importance of getting together to dance is evident since it works as a mechanism and channel of intrapersonal an interpersonal connection. In that sense, there are elements such as social stigmas, changes at the personal level, interpersonal relationships and characteristics of the dance group; In addition, connect between the members of the group. Finally, the importance of the characteristics adopted by the participants within the dance group benefits both their personal well-being and their community mental health, based on relationships with other people in areas of interaction.